2016
DOI: 10.1155/2016/3042726
|View full text |Cite
|
Sign up to set email alerts
|

Link-Polymorphism of 5-HTT Promoter Region Is Associated with Autoantibodies in Patients with Systemic Lupus Erythematosus

Abstract: Serotonin transporter linked polymorphic region (5-HTTLPR) was reported to associate with depression in systemic lupus erythematosus (SLE) patients by our team. To explore whether 5-HTTLPR plays a role in the pathogenesis of SLE, we tested 138 SLE patients and 138 age and sex matched health controls (HCs) for 5-HTTLPR by polymerase chain reaction (PCR) and agarose gel electrophoresis. Interestingly, the results suggest that the frequencies of SS genotype and S allele in SLE patients with positive anti-Sm antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In our study, there were no significant differences observed in the genotype and allele frequency of 5-HTTLPR between the SLE and HC groups. This aligns with the research findings reported by Li et al [ 18 ]. This suggests that there isn't a direct association between genetic variations in 5-HTTLPR and susceptibility to SLE.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there were no significant differences observed in the genotype and allele frequency of 5-HTTLPR between the SLE and HC groups. This aligns with the research findings reported by Li et al [ 18 ]. This suggests that there isn't a direct association between genetic variations in 5-HTTLPR and susceptibility to SLE.…”
Section: Discussionsupporting
confidence: 93%
“…Involvement of such genes as interferon-regulating factor 5 (T-receptors' signals), gene encoding protein 1, rich in H-leucine, which is repeated (gene for N-leucine-rich-repeat protein -NALP1), interferoninduced helicase C domain 1 gene -1990760 (interferoninduced helicase 1 rs1990760 -IFIH1 rs1990760), N-acetyltransferase 2 gene (N-acetyltransferase 2 -NAT2) was also confirmed. Interferon is thought to be important in the pathogenesis of SLE as well [73,76,79,80,121,126].…”
Section: Methodsmentioning
confidence: 99%
“… 15 This polymorphism has been studied in few other conditions such as irritable bowel syndrome (IBS), 16 pain severity in idiopathic trigeminal neuralgia patients, 17 and systemic lupus erythematosus. 18 However, there is no study to report the association between SERT gene polymorphism and gut motility as well as the occurrence of various GI symptoms in T2DM patients. Therefore, this study would deal with these aspects of SERT gene polymorphism in T2DM individuals.…”
Section: Introductionmentioning
confidence: 99%